2018
DOI: 10.1039/c8cc03127d
|View full text |Cite
|
Sign up to set email alerts
|

A disguised hydride in a butylmagnesium cation

Abstract: The ability of the β-CH functionality in a butylmagnesium cation [Me6TREN-Mg-n-Bu]+ to quantitatively reduce benzophenone has been demonstrated. The hydridic nature of the β-CH functionality is highlighted by its abstraction using B(C6F5)3. β-CH abstraction over alkylation in [Me6TREN-Mg-n-Bu]+ is dependent on the nature of the incoming electrophile and the polarity of the solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29] Therefore, we developed synthetic methods to access highly Lewis acidic, cationic Ae complexes which allow for intermolecular Ae-alkene interactions. While most cationic Ae metal complexes are stabilized by strong Lewis bases or strongly chelating, multidentate neutral or anionic ligands, [30][31][32][33][34][35][36][37][38][39][40][41] our interest is directed to "naked", Lewis base-free, cationic complexes. We reported cationic β-diketiminate Ae metal complexes, (BDI)Ae + , that in the presence of the weakly coordinating anion (WCA) B(C 6 F 5 ) 4 À are highly Lewis acidic and strongly bind to neutral arenes (I); BDI = HC[C(Me)N(DIPP)] 2 , DIPP = 2,6-diisopropylphenyl (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] Therefore, we developed synthetic methods to access highly Lewis acidic, cationic Ae complexes which allow for intermolecular Ae-alkene interactions. While most cationic Ae metal complexes are stabilized by strong Lewis bases or strongly chelating, multidentate neutral or anionic ligands, [30][31][32][33][34][35][36][37][38][39][40][41] our interest is directed to "naked", Lewis base-free, cationic complexes. We reported cationic β-diketiminate Ae metal complexes, (BDI)Ae + , that in the presence of the weakly coordinating anion (WCA) B(C 6 F 5 ) 4 À are highly Lewis acidic and strongly bind to neutral arenes (I); BDI = HC[C(Me)N(DIPP)] 2 , DIPP = 2,6-diisopropylphenyl (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[32] [(Me 6 TREN)MgOCHPh 2 ][B(C 6 F 5 ) 4 ] (1) was prepared according to the literature procedure. [33] Acetophenone, cyclohexanone, propiophenone, 2,2,2-trifluoroacetophenone, dicyclohexyl ketone, 2,5-hexanedione, 2-methyl-3-pentanone, 1,3-dichloroacetone and 2-pentanone were dried in CaH 2 or Na 2 CO 3 with 0.5 mol% of KMnO 4 before distilling. Benzophenone, 4,4'-dichloro benzophenone, benzil, and 4,4'-dimethyl benzophenone were recrystallized in dry diethyl ether and dried under vacuum using Schlenk technique before use.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, [(Me 6 TREN)MgCH 2 CH 2 C 2 H 5 ][B(C 6 F 5 ) 4 ] was shown to reduce benzophenone through its hydridic β-CH functionality resulting in the monomeric alkoxomagnesium compound, [(Me 6 TREN)MgOCHPh 2 ][B(C 6 F 5 ) 4 ] (1, Scheme 1). [16] While 1 is coordinatively saturated, the hemilabile nature of Me 6 TREN [17,18] provides an opportunity to explore the potential reactivity of an alkoxomagnesium species, in a controlled manner. We chose to investigate ketone hydroboration, a wellexplored and well-established reaction in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…This reactivity, however, has been largely restricted to the reduction of heteroatom-containing CE (e.g., E = O, , NR ) and CE (E = O, , N , ) multiple bonds and, although the transition-metal-promoted addition of alkenes to MgH 2 has been described, definitive examples of the hydromagnesiation of less polarized carbon–carbon multiple bonds are more limited. The terminal Mg–H bonds of compounds 5 and 6 have been reported by the groups of Okuda and Parkin, respectively, to react with styrene. , Both of these reactions take place at room temperature and within minutes to yield either selective formation of the magnesium 1-phenylethyl derivative (for 5 ) or a mixture of the 1-phenylethyl and 2-phenylethyl derivatives (for 6 ). We have very recently observed that the dimeric BDI derivative 1 reacts similarly with a significant range of terminal n- alkenes, to provide access to the corresponding halide-free magnesium organometallics .…”
Section: Introductionmentioning
confidence: 93%
“…The chemistry of molecular saline hydrides has advanced significantly during the past decade . Whereas the synthesis and structures of the first strontium and barium hydrides have only recently been established, a wide range of lighter magnesium and calcium species are now available for study such that a diverse and unique reaction chemistry is also starting to emerge. , The exploitation of β-diketiminate (BDI) derivatives such as compounds 1 – 4 (Chart ) has been central to these latter advances, allowing the development of a wide range of novel stoichiometric and catalytic processes. The dimeric magnesium hydride ( 1 ) in particular has enabled a plethora of hydrosilylation and hydroboration chemistries. This reactivity, however, has been largely restricted to the reduction of heteroatom-containing CE (e.g., E = O, , NR ) and CE (E = O, , N , ) multiple bonds and, although the transition-metal-promoted addition of alkenes to MgH 2 has been described, definitive examples of the hydromagnesiation of less polarized carbon–carbon multiple bonds are more limited.…”
Section: Introductionmentioning
confidence: 99%